2003
DOI: 10.1080/00365520310001734
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoid in a Young Woman with Systemic Lupus Erythematosus and Atrophic Autoimmune Gastritis

Abstract: The fact that it mostly concerns (relatively) young patients may suggest a potential causative relation between those autoimmune disorders and the early development of atrophic gastritis with hypergastrinaemia, which subsequently leads to the occurrence of gastric carcinoid tumours at a young age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Furthermore, the prevalence and the association of SLE and AIG itself are still unclear. The association of SLE and type I gastric carcinoid has rarely been reported previously (5,7,8). Although all three previously reported cases with type I gastric carcinoid with AIG and SLE showed pernicious anemia at the time of finding carcinoids (5, 7, 8), in the present case, vitamin B12 was low but pernicious anemia was not present when the carcinoid was detected, indicating that gastric carcinoid possibly occurred before the induction of pernicious anemia.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Furthermore, the prevalence and the association of SLE and AIG itself are still unclear. The association of SLE and type I gastric carcinoid has rarely been reported previously (5,7,8). Although all three previously reported cases with type I gastric carcinoid with AIG and SLE showed pernicious anemia at the time of finding carcinoids (5, 7, 8), in the present case, vitamin B12 was low but pernicious anemia was not present when the carcinoid was detected, indicating that gastric carcinoid possibly occurred before the induction of pernicious anemia.…”
Section: Discussionmentioning
confidence: 38%
“…Therefore, the average age at detection of gastric carcinoids is in the 60s (3), and it rarely occurs at younger ages. In cases with other autoimmune disorders (4,5), type I gastric carcinoids may develop at a relatively young age. Pernicious anemia is usually already present when type I gastric carcinoid is detected.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed 14 cases of gastric cancer associated with SLE, consisting of 10 females and four males (aged 23‐72 years) . There were nine cases of adenocarcinoma, four cases of carcinoid tumor, and one case of neuroendocrine carcinoma of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“… Additional solid tumors have been reported in patients with systemic lupus erythematosus: biliary tract, 143 brain, 135,137,161 carcinoid (gastric), 171,172 colon, 133,135,137,140,142,143,152,153,161,173 connective tissue, 137 endocrine, 137 esophagus, 135,137 eye, 137 heart, 137 kidney, 133,135,137,139,142,152 lacrimal gland, 142 larynx, 135,137,161 melanoma, 135,137,143,174 oral, 135,137,142 pancreas, 133,135,137,139,142,152 rectum, 135,137,141 stomach, 135,137,142,143,153,161 testicles, 137,142 thyroid, 137,139,142,152,153,161 thymus, 175 urinary bladder, 135,137 and uterus 135,137,139,142,161 …”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%